2019
DOI: 10.21926/obm.geriatr.1903066
|View full text |Cite
|
Sign up to set email alerts
|

Personalised Medicine for Dementia: Collaborative Research of Multimodal Non-pharmacological Treatment with the UK National Health Service (NHS)

Abstract: The dominant narrative around dementia argues that progression cannot be halted or reversed. However, evidence on multimodal non-pharmacological treatments formulated around a 'personalised medicine' approach challenges this view. This paper reviews the current evidence for dementia prevention utilising such treatments and explains the logic of applying personalised medicine. The functional medicine treatment approach to 'root cause' analysis is presented as currently practiced with patients experiencing cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 94 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Prior studies have demonstrated reversal of cognitive decline, improved memory and quality of life with a personalised multimodal approach (Bredesen et al 2016;Bredesen et al 2018) [16,17]. While the above studies occurred in the Netherlands and North America, the current study builds upon recent case reports in the UK demonstrating improvements in symptoms of memory decline from a personalised multimodal approach [18].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Prior studies have demonstrated reversal of cognitive decline, improved memory and quality of life with a personalised multimodal approach (Bredesen et al 2016;Bredesen et al 2018) [16,17]. While the above studies occurred in the Netherlands and North America, the current study builds upon recent case reports in the UK demonstrating improvements in symptoms of memory decline from a personalised multimodal approach [18].…”
Section: Introductionmentioning
confidence: 83%
“…To further elucidate needs and views going forward, a deliberative workshop and feedback interviews were held to present preliminary findings of the earlier interviews and focus groups to participants, and to hear their reflections and further thoughts on framing a future vision for dementia treatment. Within this workshop preliminary findings were also presented from recently completed case reports mentioned above [18]. We involved a purposive sample of 49 participants (Table 2) in 32 interviews, 3 focus groups and a deliberative workshop.…”
Section: Designmentioning
confidence: 99%